1998
DOI: 10.1042/bj3360429
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the C-terminal domains of human dihydrodiol dehydrogenase isoforms in the binding of substrates and modulators: probing with chimaeric enzymes

Abstract: Human liver dihydrodiol dehydrogenase (DD; EC 1.3.1.20) exists in isoforms (DD1, DD2 and DD4) composed of 323 amino acids. DD1 and DD2 share 98% amino acid sequence identity, but show lower identities (approx. 83%) with DD4, in which a marked difference is seen in the C-terminal ten amino acids. DD4 exhibits unique catalytic properties, such as the ability to oxidize both (R)- and (S)-alicyclic alcohols equally, high dehydrogenase activity for bile acids, potent inhibition by steroidal anti-inflammatory drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 32 publications
0
37
0
Order By: Relevance
“…For example, a study by Matsuura et al, (1998), which used chimeric enzymes produced by switching the C-terminal loop in AKR1C4 with that of AKR1C1, demonstrated that the binding of substrates, inhibitors, and activators of AKR1C4 requires the amino acid residues located in the C-terminal loop of the wild-type AKR1C4 enzyme, such as Leu311. Furthermore, Matsuura et al found that a leucine to valine mutation in amino acid 311 (L311V) decreased the catalytic activity of AKR1C4 for its substrates, but did not affect the enzyme's sensitivity to an inhibitor or affect the enzyme's response .…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study by Matsuura et al, (1998), which used chimeric enzymes produced by switching the C-terminal loop in AKR1C4 with that of AKR1C1, demonstrated that the binding of substrates, inhibitors, and activators of AKR1C4 requires the amino acid residues located in the C-terminal loop of the wild-type AKR1C4 enzyme, such as Leu311. Furthermore, Matsuura et al found that a leucine to valine mutation in amino acid 311 (L311V) decreased the catalytic activity of AKR1C4 for its substrates, but did not affect the enzyme's sensitivity to an inhibitor or affect the enzyme's response .…”
Section: Discussionmentioning
confidence: 99%
“…Enzymes and Their Assays The recombinant AKR1C1, 18) AKR1C2, 17) AKR1C3, 14) AKR1C4 19) and chimeric AKR1C1 with the C-terminal 39 residues of AKR1C4 18) were prepared and purified to homogeneity as Product Identification To identify reaction products, ketosteroid reduction was conducted in a 2.0 ml system containing 0.1 M potassium phosphate, pH 7.0, 2.0 mM NADPH, 15 mM steroid substrate and enzyme (10 mg). The substrate and products were extracted into 8 ml ethyl acetate 15, 30 or 60 min after the reaction was started at 37°C, and the resulting extract was evaporated to dryness.…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the Cterminal region of AKR1C1 is a component of the substratebinding pocket. 18) The chimeric AKR1C1, which exchanges the C-terminal 39 residues with those of AKR1C4, was significantly resistant to the inhibition by diazepam, medazepam and estazolam, showing respective IC 50 values of 44, 15 and 128 mM. Thus, the benzodiazepines may interact with the flexible C-terminal loop of the enzyme, 18,22) and the structural change induced by the binding of the drugs might be included in the mechanistic steps of the inhibition.…”
mentioning
confidence: 99%
“…Mouse 3(17)aHSDs share high amino acid sequence identity (69-75%) with rat 3a-HSD (AKR1C9), human 3(20)a-HSD (AKR1C1) and human 3a-HSDs (AKR1C2, AKR1C3 and AKR1C4) and rabbit 3a/17b/20a-HSD (AKR1C5). Recent crystallographic and site-directed mutagenesis studies of AKR1C1, 28) ) of the mouse enzymes differs from those of the other HSDs, and may also be related to the substrate specificity, because the importance of the C-terminal residues for the discrimination of the incoming steroid substrates has been suggested by crystallographic and site-directed mutagenesis studies of AKR1C5, 31) AKR1C1 28,32) and AKR1C4.…”
mentioning
confidence: 99%